Analyzing morphometry among extant and extinct species: A case study of genus Agassizia (Spatangoida: Echinoidea) - Martinez-Melo, Alejandra (2024)
Introduction: The genus Agassizia in Mexico is represented both in the fossil record with the species Agassizia regia† during the Miocene of Chiapas and in the extant species Agassizia excentrica on the Atlantic coast and Agassizia scrobiculata on the Pacific coast. Qualitative diagnosis and descriptions make it hard to distinguish morphological boundaries between species, especially in groups with fossils and recent representatives, increasing the level of complexity by having samples of disparate qualities and quantities. Objective: We propose the use of little explored statistical methods in the comparison of paleontological and biological populations. This methodology allowed us to resolve issues of missing values in a morphometric data set for the genus Agassizia. Methods: Using samples recently collected and specimens already housed in collections, we explore a routine of recovery of missing data MICE and the numerical and graphic analyses PERMANOVA, PCA, and SIMPER to compare morphometric parameters between these species for recognizing diagnostic characters. Results: Our results show a clear morphological difference in the length of the ambulacrum II and the length and width of the periproct and peristome structures, these being greater in A. scrobiculata, with a consistent pattern in both population samples not previously described. Conclusions: Quantitative morphometric comparisons can be an assertive and complementary tool to determine distinctive differentiation characteristics in species of the same genus. Comparative morphology reviews should be an ongoing exercise to keep taxonomic knowledge on both extinct and extant species up to date. Our research encourage the scientific community studying fossil populations to utilize quantitative and multivariate methods to strengthen their investigations.